1994
DOI: 10.1088/0953-8984/6/10/016
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion, the Kirkendall effect and vacancy jump frequency ratios in dilute Al-Zn alloys

Abstract: The method of vapour-solid couples was applied in order to investigate interdiffusion and intrinsic diffusion in dilute Al-Zn alloys. Although an aluminium oxide layer could not be avoided in our experiments, typical concentration-penetration curves were measured by electron probe microanalysis. The Boltzmann-Matano evaluation of the profiles yielded interdiffusion coefficients in agreement with previously published results. Contrary to the expected behaviour, bulges were observed by metallographic inspection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The first example describes the semi-infinite vapor-solid diffusion couple con-structed by Hagenschulte and Heumann. [38] The calculation (Fig. 7) is in remarkable agreement with the measured concentration curve.…”
Section: Simulations Of the Diffusion Experimentssupporting
confidence: 77%
See 3 more Smart Citations
“…The first example describes the semi-infinite vapor-solid diffusion couple con-structed by Hagenschulte and Heumann. [38] The calculation (Fig. 7) is in remarkable agreement with the measured concentration curve.…”
Section: Simulations Of the Diffusion Experimentssupporting
confidence: 77%
“…Though their data appear to be comparatively scattered, the same concentration tendency was confirmed. The last chemical diffusion coefficient measurement by Hagenschulte and Heuman [38] was accomplished by extracting data from a Boltzmann-Matano evaluation of the penetration profile; however, a comparison indicates this set of data does not extrapolate to the proper tracer diffusivity of Zn and was therefore excluded from the present assessment. …”
Section: Chemical Diffusion Coefficientmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed no chemical interaction at UO 2 /Fe interface after 1000-hour annealing at 1000 o C [12]. As to be discussed, the existence of UO 2 will influence interface reaction by introducing an incubation time period for diffusion and this effect must be considered in data interpretation.…”
Section: Methodsmentioning
confidence: 95%